Multiple objective decision support framework for configuring, loading and reconfiguring manufacturing cells - Baykasoğlu, Adil (1999)
The potential advantages of Cellular Manufacturing Systems (CMS) are very well known in industry. However it is also shown that their performance is very sensitive to changing production requirements. The detrimental effects of changing production requirements on the performance of CMS can be alleviated by "implementing better manufacturing cell designs", "employing effective part loading strategies" and "reconfiguration".